Living water : images, symbols, and settings of early Christian baptism - Jensen, Robin Margaret, 1952- (Vigiliae Christianae, Supplements, 2011)
This general survey of early Christian baptismal iconography and architecture integrates visual depictions and physical settings of baptism with textual evidence for its practice and purpose. An opening overview of pictorial art (paintings, relief sculpture, mosaics, and ivories) prompts questions about components of the actual ritual which are treated in the literary sources. The study's second half considers selected baptismal structures, examining the symbolism, purpose, and possible meaning of their spatial design and decorative programs. In most instances the synthesis of documentary and material evidence is enriching and complementary. However, even when physical and textual data diverge, their discontinuity demonstrates the variability of ritual performance and the perennial distinction between ideal and actual practice..